Accreditation of engineering programs: an evaluation of current practices in Malaysia - Mohd Said, S.; Chow, Chee-Onn; Mokhtar, N.; Ramli, R.; Tuan Ya, T.M.Y.S.; Mohd Sabri, M.F. (International Journal of Technology and Design Education, 2011)
The curriculum for undergraduate engineering courses in Malaysia is becoming increasingly structured, following the global trend for quality assurance in engineering education, through accreditation schemes. Generally, the accreditation criteria call for the graduates from engineering programs to demonstrate a range of skills, from technical problem solving to soft skills and an aptitude for lifelong learning. In order to comply with these criteria, accreditation schemes are adopted as a quality assurance measure. This paper shall introduce the characteristics of the engineering accreditation scheme in Malaysia. The impact of the accreditation scheme on the quality of these engineering programs shall be evaluated. Data collection is in the form of benchmarking and questionnaires. The evaluation criteria shall be in terms of benefits to the institution, academic faculty, students, and the challenges encountered. A discussion on the evaluation shall include the supposed dichotomies which arise from this accreditation process, namely the compromise between research versus teaching; and the value of engineering knowledge whether as an academic pursuit or catering to industry's needs. Ultimately, this paper shall address a fundamental question related to undergraduate teaching in engineering: whether accreditation is a necessary prerequisite in maintaining high standards in engineering programs in Malaysia.